Multimedia issues over bluetooth (video streaming) - Haque, Md. Nazmul; Hasan, Md. Mehedi (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.